State Officials Asset Disclosure: Evidence from China - Widodo, Selamat; Nugroho, Hibnu; Raharjo, Agus; Prayitno, Kuat Puji; Zulhuda, Sony; Liu, Jie (Lembaga Contrarius Indonesia, 2024)
This study examines the anti-corruption movement's effect on state officials' asset reporting in Indonesia and China. The purpose of this study is to explore the impact of asset reporting on the level of corruption in Indonesia and compare the impact of asset disclosure on the level of corruption in China. The method used in this study is the normative juridical method. In Indonesia, we found that the reporting of assets official assets anti-corruption movement shows that despite the obligation to make asset reports for state officials, the level of corruption in Indonesia is still high. In China, there is a decrease in corruption in asset disclosure, an essential instrument of wealth transparency, preventing conflicts of interest, and upholding ethical standards in both the public and private spheres. Asset disclosure serves as a deterrent to corruption, maintains public trust, and ensures that individuals in positions of responsibility act in the best interests of the public or stakeholders they serve, statistically decreasing corruption rates in China. This study provides evidence of anti-corruption benefits from an asset reporting perspective, which can be helpful for governments seeking to improve anti-corruption innovation.